Effects of hyperglycemia and ageing on the healing of colonic anastomoses in rats - Biondo-Simões,Maria de Lourdes Pessole (2009)
INTRODUCTION: Despite the significant advances in the knowledge of the healing process, there is a limited number of studies demonstrating the relationships of this healing with ageing and elevated levels of glycemia. PURPOSE: To evaluate the effects of ageing and hyperglycemia on the healing of colonic anastomosis. METHODS: 138 young and old male rats were utilized. Some of them were normoglycemic and others had hyperglycemia induced by streptozocin (50mg/kg). They were maintained under control for 90 days. They were then submitted to a termino-terminal anastomosis in the left colon. On the third, seventh and fourteenth days after surgery, their resistance was evaluated and a histopathological study of the anastomosis was carried out. RESULTS: Gain in resistance was similar for both groups. The additive effect of age with hyperglycemia made a significant difference to the collagen I (p<0.001), III (p=0.022) and total (p<0.001). Among the old animals, the glycemia was a determining factor for the occurrence of a significant difference in total collagen (p=0.029) and collagen I (p=0.013). Among the normoglycemics, age determined a lower density of collagen I (p=0.002). CONCLUSION: There is delayed collagen synthesis and maturation of the scars of older animals, a situation that becomes more serious in older hyperglycemic animals, but insufficient to adversely affect the gain in resistance.